Afebrile tuberculous prostatic abscess with rectal fistula after intravesical Bacillus Calmette‐Guérin immunotherapy - Tatsuhiro Sawada; Ayaka Igarashi; Seiji Arai; Akira Ohtsu; Yuji Fujizuka; Shun Nakazawa; Yoshitaka Sekine; Hidekazu Koike; Yosuke Furuya; Kazuhiro Suzuki (IJU Case Reports)
Introduction Intravesical Bacillus Calmette‐Guérin immunotherapy is generally a safe treatment for non‐muscle‐invasive bladder cancer but sometimes causes complications. Case presentation The patient was an 80‐year‐old man who had undergone Bacillus Calmette‐Guérin immunotherapy for non‐muscle‐invasive bladder cancer. Two months later, he developed an irregular pelvic mass surrounding the prostate and rectum with no fever. A colonoscopy showed purulent mucus discharge in the lower rectum, and a CT‐guided needle biopsy revealed epithelioid granuloma containing Langhans giant cells. Although acid‐fast bacteria culture and PCR of biopsy samples were negative, he was clinically diagnosed with Bacillus Calmette‐Guérin‐related tuberculous prostatic abscess spreading to the rectum. After receiving combined antitubercular drugs for 6 months, his discomfort disappeared with almost complete shrinkage of the prostatic abscess. Conclusion Tuberculous prostatic abscess is a rare complication associated with Bacillus Calmette‐Guérin immunotherapy and sometimes induces rectal fistula. Conservative treatment with antitubercular drugs is efficient and safe for treatment of tuberculous prostatic abscess.